Determination of total phenol, condensed tannin and flavonoid contents and antioxidant activity of Uncaria gambirextracts - M. Jain Kassim; M. Hazwan Hussin; A. Achmad; N. Hazwani Dahon; T. Kim Suan; H. Safley Hamdan (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2011)
Uncaria gambir, a well known Southeast Asia plant have been previously used as an alternative medicine for treatment such as diarrheal, sore throat and spongy gums. Due to its useful properties, in this study we have analysed the total phenol, condensed tannin, flavonoid content and antioxidant activity of Uncaria gambir in three different solvent extracts. Characterization and quantification analysis using Fourier Transform Infrared (FTIR) spectroscopy and reverse phase-high performance liquid chromatography (RP-HPLC) has confirmed that the major chemical constituents of Uncaria gambir are mainly catechins. It was revealed that the ethyl acetate gambir extract gives the highest catechin content and antioxidant activity compared with other solvent extracts.Key words: Uncaria gambir, antioxidant activity, condensed tannin, flavonoid